Long non-coding RNA ROR decoys gene-specific histone methylation to promote tumorigenesis. Issue 1 (December 2015) - Fan, Jiayan; Xing, Yue; Wen, Xuyang; Jia, Renbin; Ni, Hongyan; He, Jie; Ding, Xia; Pan, Hui; Qian, Guanxiang; Ge, Shengfang; Hoffman, Andrew; Zhang, He; et al.
Abstract Background Long non-coding RNAs (lncRNAs) are not translated into proteins and were initially considered to be part of the 'dark matter' of the genome. Recently, it has been shown that lncRNAs play a role in the recruitment of chromatin modifying complexes and can influence gene expression. However, it is unknown if lncRNAs function in a similar way in cancer. Results Here, we show that the lncRNAROR occupies and activates theTESC promoter by repelling the histone G9A methyltransferase and promoting the release of histone H3K9 methylation. Suppression ofROR in tumors results in silencing ofTESC expression, and G9A-mediated histone H3K9 methylation in theTESC promoter is restored, which significantly reduces tumor growth and metastasis. WithoutROR silencing, TESC knockdown presents consistent and significant reductions in tumor progression. Conclusions Our results reveal a novel mechanism by whichROR may serve as a decoy oncoRNA that blocks binding surfaces, preventing the recruitment of histone modifying enzymes, thereby specifying a new pattern of histone modifications that promote tumorigenesis.